High altitude balloon testing of Arduino and environmental sensors for CubeSat prototype. (October 2022) - Lay, Kenjiro S.; Li, Lingqi; Okutsu, Masataka
Graphical abstract: Highlights: A flight experiment on Arduino and sensors was conducted using a weather balloon. The high altitudes offer conditions that are similar to those of space. Thermal and barometric data were collected during the flight. The calculated pressure altitudes were validated against the GPS altitudes. Abstract: CubeSats were conceived with an aim to provide students with hands-on, design, build, and test experiences on spacecraft. Many education-class CubeSats keep the cost of the projects low with the use of commercial off-the-shelf (COTS) products. But using parts not designed for space missions often means a compromise in performance (e.g., low sensor accuracy, low power efficiency) and reliability, which makes component testing a necessary part of the development process. Unfortunately, there is no single lab equipment that can test the integrated features of CubeSats, including the radio communication over ranges of altitudes and distances. It has been pointed out that a high altitude reached by a weather balloon offers an environment similar to the space environment. This paper describes a balloon flight testing of Arduino and sensors for a CubeSat "prototype"—a preliminary mock-up model used for hardware selection and validation during the initial building phase. Atmospheric pressures and temperatures were measured throughout the balloon flight. The measured pressures were validated by comparing Arduino's pressure altitudes against the GPS altitudes, and the measured temperatures were assessed against the standard atmosphere model.